REVITALIZACIÓN SINDICAL EN ARGENTINA: EL CASO DEL SUBTE - Arias, Cora Cecilia; Salgado, Paula Dinorah (Universidad de Costa Rica, 2012)
This paper set out and describes the international scholar’s debates about “trade un ionrevitalization ”. Particulary, it addresses the usage of the concept in Argentinian research. After stating the theoretical question, a particular empirical experience is analyzed: the case of the rank-and-file organization of the subway workers of Buenos Aires. The aim is to debate on analytical potentialities of tackled theoretical standpoints.